Nitrogen fixation associated with two cohabiting moss species expresses different patterns under Cu and Zn contamination - Toke Due Sjøgren; Yinliu Wang; Kathrin Rousk (Environmental Science and Pollution Research, 2023)
Nitrogen (N 2 ) fixation by moss-associated cyanobacteria is an important N source in pristine ecosystems. Previous studies have shown that moss-associated N 2 fixation is sensitive to anthropogenic N pollution. However, we still lack understanding of the effects of other factors derived from anthropogenic sources, such as heavy metal pollution on N 2 fixation. To test this, we collected two dominant mosses ( Pleurozium schreberi and Spaghnum palustre ) from a temperate bog in Denmark and assessed their N 2 fixation responses to simulated heavy metal pollution by adding 5 levels (plus a control) of copper (Cu, 0–0.05 mg g dw −1 ) and zinc (Zn, 0–0.1 mg g dw −1 ). Metal concentrations in both mosses increased linearly with Cu and Zn addition, but N 2 fixation activity associated with S. palustre was to a greater extent negatively affected by both Cu and Zn additions than that associated with P. schreberi . Copper additions even promoted N 2 fixation in P. schreberi . Hence, the heavy metal sensitivity of N 2 -fixing cyanobacteria is dependent on the host moss-species, and the vulnerability of ecosystems towards heavy metal pollution could vary depending on the dominant moss species.